INVESTIGATING DIGITALIZED AND CONVENTIONAL ERGONOMIC PRACTICES IN PREVENTING WORK POSTURE RELATED MUSCULOSKELETAL PROBLEMS FROM OCCUPATIONAL HEALTH NURSING APPROACH: A SCOPING REVIEW - Ni Luh Dwi Indrayani; Chi Jane Wang; Apiradee Pimsen; I Gede Putu Darma Suyasa; Ni Luh Putu Inca Buntari Agustini; I Ketut Swarjana (Universitas Airlangga, 2026)
Introduction: Occupational health nurses address ergonomic risks, yet research comparing digital and conventional work practices across job sectors remains limited. This study aims to systematically search existing literature on digitalized and conventional ergonomic practices across occupations to identify strategies for preventing musculoskeletal disorders. Method: A scoping review was conducted to identify the key elements of digitalized and conventional ergonomic practices, extracted by using method used, countries, job categories, and body areas most frequently studied. A systematic searching methodology was conducted utilizing five databases. Search strategies were developed using controlled vocabularies based on Emtree and MeSH terms, to identify relevant keywords and subject headings up to the year 2025. Study selection process predefined inclusion and exclusion criteria. To ensure methodological rigor and transparency, the review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Result: Twenty-two studies were included, revealing three core elements-physical, cognitive, and organizational ergonomics- in both digitalized and conventional ergonomic practices across occupations. The corresponding sub-elements highlighted the growing role of technology in the evolution of ergonomic practices, with digital approaches more prevalent in healthcare and office settings, while conventional strategies dominated in industrial environments. Most studies focused on physical ergonomics, particularly posture correction, exercise therapy, and workstation modifications. Most of studies used pain measurement as the primary study outcome that achieved through educational interventions, ergonomic job rotation, and work schedule adjustments. Conclusion: Ergonomic practices with digitalized and conventional strategies offer actionable recommendations for human factors in working environments, to prevent musculoskeletal pain related to working posture, benefiting occupational health professionals and providing a foundation for future meta-analyses on specific interventions. Keywords: ergonomics; musculoskeletal pain; occupational health nursing; practices.